A menekültügyi őrizet elrendelésének anyagi jogi feltételei az uniós jog tükrében - Kiss, Árpád (Debreceni Jogi Műhely, 2015)
Hungary lies in the route of the stream of refugees coming from the Balkan. It is a transit country, so the refugees do not typically intend to stay here, they rather wish to travel torwards to West- and North Europe. Particular sections of Hungary’s border also mean the external borders of the European Union, the area of freedom, security and justice, which has a common asylum system. Significant part of illegal immigrants presents asylum claim only to avoid the aliens procedures. From the 1st of January 2013, the legislature terminated the aliens detention against asylum applicants. From 1st of July 2013 the Hungarian legislature reintroduced the possibility of detention of applicants. The new regulation has been placed in Act LXXX of 2007 on the Right of Asylum, Sections 31/A-31/H by Act XCIII of 2013 on the Amendment of Particular Laws Concerning Law Enforcement. The introduction of asylum-seeker detention and the practice of its application have raised dust. In my essay I am introducing the connections between the reasons of ordering asylum-seeker detention in the Act on Asylum and its backgroud in the EU Directive. I am not dealing with the question of compatibility of asylum detention and human rights and with problematic procedural issues, because I consider it more important to review the substantive conditions of asylum-seeker detention and the certain practical questions of its application therefore I am focusing on this segment of jurisdiction.